Spinal cord trauma in dogs and cats: revision of pathophysiology and medical treatment - Arias, Mônica Vicky Bahr; Severo, Maíra Santos; Tudury, Eduardo Alberto (Semina: Ciências Agrárias, 2007)
Spinal cord trauma is one of the most frequent and serious neurologic entity in clinical practice, due to its production of lesions. Acute spinal cord injury initiates a sequence of vascular, biochemical and inflammatory events that can take to disastrous and frequently irreversible consequences to the motor and sensorial function of the animal. Acute spinal cord trauma should be considered an emergency and fast and appropriate intervention, in an appropriate interval of time, can limit the extension of the damage to the neuronal tissue, favoring neurological recovery. In general, the treatment of spinal cord involves the use of neuroprotective agents to control secondary lesions; and to perform surgery aiming decompression of the injured spinal cord, accomplishing or not the stabilization of the spine. Chronic spinal cord compression may be secondary to diseases that develops gradually, or refers to the effects of spinal cord trauma in the months to years after the acute injury. The main purpose of this paper was to revise the pathophysiology of spinal cord trauma, the medical treatment available, the options for the future and the controversies about the use of some drugs.